FFRCT and recurrent symptoms in patients with stable chest pain. (3rd October 2022) - Madsen, K T; Noergaard, B L; Oevrehus, K A; Parner, E; Jensen, J M; Grove, E L; Fairbairn, T A; Nieman, K; Patel, M; Rogers, C; Mickley, H; Thomsen, K K; et al.
Abstract: Introduction: The major benefit of coronary revascularization when compared with optimal medical treatment (OMT) in patients with stable chest pain (CP) relates to improvement of symptoms and reduction of reinterventions. Non-invasive methods are warranted to discriminate between patients at low and high risk of recurrent CP for subsequent guidance of antianginal treatment (invasive or OMT). Purpose: To evaluate the association between coronary CT angiography (CTA) derived fractional flow reserve (FFRCT), recurrent CP and quality of life (QOL) in patients with new onset stable CP and stenosis by CTA. Methods: Multicenter cohort 3-year follow-up sub-study of 769 patients from the Assessing Diagnostic Value of Non-invasive FFRCT in Coronary Care (ADVANCE) registry at three Danish sites, the "ADVANCE-DK Registry". All patients had at least one ≥30% coronary stenosis by CTA and underwent subsequent core laboratory FFRCT analysis by HeartFlow. An abnormal FFRCT was defined as the lowest in vessel FFRCT value ≤0.80. Patients were classified according to completeness of revascularization by FFRCT: 1) completely revascularized (CR-FFRCT), all coronary arteries with an abnormal FFRCT test result revascularized; 2) incompletely revascularized (IR-FFRCT), ≥1 coronary artery with an abnormal FFRCT test result not revascularized. All patients completed the Seattle Angina Questionnaire (SAQ-7), the EuroQol questionnaire (EQ-5D-5L) and graded (0–100) overall health using the EQ VAS scale at 3-year follow-up. Recurrent CP was defined as CP within the last 4 weeks prior to this follow-up. Results: Patient characteristics are given in Table 1. At follow-up 23% patients reported recurrent CP. An abnormal vs a normal FFRCT increased the risk of recurrent CP, 27% vs 15%, RR: 1.82; 95% CI: 1.31–2.52, p<0.001. Amongst patients with abnormal FFRCT, revascularization (+/−) was associated to a numerical, but not statistical significantly, reduced risk of recurrent CP, 23% vs 30%, RR: 0.76; 95% CI: 0.56–1.03, p=0.07. IR-FFRCT vs CR-FFRCT had a higher risk for recurrent CP, 31% vs 13%, RR: 2.34; 95% CI: 1.48–3.68, p<0.001, whilst no difference was observed for CR-FFRCT vs normal FFRCT, 13% vs 15%, RR: 0.92; 95% CI: 0.54–1.54, p=0.74. IR-FFRCT vs CR-FFRCT or normal FFRCT, had lower SAQ-7, EQ-5D-5L and EQ-VAS scores, Table 1, all p<0.005. Scores for three selected SAQ-7 domains are shown in Figure 1. Use of antianginal medicine was higher in IR-FFRCT compared to CR-FFRCT and normal FFRCT, mean ± SD: 1.2±0.05 vs 1.0±0.04, p=0.02. Conclusion: An abnormal FFRCT identifies patients with an increased risk of recurrent CP up to 3 years after index testing. Completeness of revascularization by FFRCT reclassifies patients with abnormal FFRCT into groups with low and high risk for recurrent CP and impaired QOL. Funding Acknowledgement: Type of funding sources: None.